Proposing a design framework for smartphone AR browsers used in unfamiliar urban tourism destinations:Powerpoint - Buhalis, D. (University of Twente, 2020)
This lecture presents: Advantages of hand-held ar for tourism; Challenges & gaps; Methodology; Route, tasks & targets; Ar browsers & participants; Procedure, time & equipment; Key results.